Gamified Language Learning Applications: Enhancing Motivation and Speaking Skills of First-Semester Informatics Engineering Students at Politeknik Negeri Bengkalis - Desi Wahana; pretti Ristra (Universitas Maritim Raja Ali Haji (UMRAH), 2026)
This study investigates the impact of gamified language learning applications on the motivation and speaking skills of first-semester Informatics Engineering students at Politeknik Negeri Bengkalis. Using a quasi-experimental design with 60 participants, the study compared an experimental group using gamified apps like ELSA Speak and Duolingo against a control group following conventional methods. Quantitative data from pretests and posttests were analyzed using independent-sample t-tests, while qualitative insights were gathered through structured questionnaires. The results revealed a transformative effect: the experimental group achieved significantly higher t-test scores in motivation (t=8.76, p<0.001) and speaking proficiency (t=9.12, p<0.001) compared to the control group. These findings were reinforced by a